2013
DOI: 10.7326/0003-4819-159-3-201308060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Estimates of Benefit From Preventive Care Guidelines

Abstract: Models of personalized preventive care may illustrate how magnitude and rank order of benefit associated with preventive guidelines vary across recommendations and patients. These predictions may help clinicians to prioritize USPSTF recommendations at the patient level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 30 publications
1
58
0
Order By: Relevance
“…Of course, the time available in clinical practice to discuss and provide the numerous preventive care recommendations is inadequate. 75 This makes prioritization and personalization of preventive care all the more essential, allowing more time to be spent on medical care that is most likely to help an older individual achieve his/her goals and is least likely to cause harm.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the time available in clinical practice to discuss and provide the numerous preventive care recommendations is inadequate. 75 This makes prioritization and personalization of preventive care all the more essential, allowing more time to be spent on medical care that is most likely to help an older individual achieve his/her goals and is least likely to cause harm.…”
Section: Discussionmentioning
confidence: 99%
“…The large potential health benefit from tailored care strategies in the subgroup with co-occurring alcohol misuse, smoking, and depression could warrant additional systems and provider burdens they may impose. Indeed, it has been suggested that refining screening, surveillance, and treatment strategies for this subgroup such as making them more patient-centered and prioritized, has great potential to improve population health [8]. But no group has considered whether discontinuation of one behavior is associated with the discontinuation of these other behaviors, a question of central importance in the efficient and effective design of interventions.…”
Section: Introductionmentioning
confidence: 99%
“…1–11 The potential benefit from these clinical interventions may not be achieved for many years, but the potential harms may occur in the short term. 3,4,7,12 Thus, without considering long-term prognosis , defined as prognosis regarding life expectancy in the range of years, patients with limited life expectancy may be inappropriately exposed to harm from continued clinical interventions with little chance of benefit, whereas stopping these interventions in healthy older adults with long life expectancy may exclude them from potentially beneficial interventions.…”
mentioning
confidence: 99%